2009
DOI: 10.1111/j.1365-2834.2008.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

New graduate transitions: leaving the nest, joining the flight

Abstract: Nurse Managers must question why the disenfranchisement and marginalization of new graduates continues. Persistent inertia impacts recruitment and retention of graduate nurses and patient safety, transforming episodic challenges into chronic systemic issues. This article will contribute to new nursing knowledge by providing a Canadian perspective of demographic trends of the Registered Nurse (RN) and salient actions required to resolve the discourse of new graduate transition into the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 36 publications
(52 reference statements)
0
78
0
1
Order By: Relevance
“…Yet, because of workforce shortages and fiscal constraints, new graduates may be expected to make the transition seamlessly (Wolff et al, 2010) and take on increased responsibility prematurely (Bates, 2005). Given this, graduates may have little access to support and preceptorship (Morrow, 2009;Etheridge, 2007). They may lack the recommended multiple clinical experiences (Etheridge, 2007) and the time to practise skills, adapt to the new role and gain confidence (Thomka, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, because of workforce shortages and fiscal constraints, new graduates may be expected to make the transition seamlessly (Wolff et al, 2010) and take on increased responsibility prematurely (Bates, 2005). Given this, graduates may have little access to support and preceptorship (Morrow, 2009;Etheridge, 2007). They may lack the recommended multiple clinical experiences (Etheridge, 2007) and the time to practise skills, adapt to the new role and gain confidence (Thomka, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests a relationship between patient safety and number of years of practice. [11][12][13] Patient mortality is highest among RNs with 2 or fewer years of experience. [14] Background Confidence is one of the most influential motivators of behavior a novice RN can possess.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in patient acuity has been well documented in the literature [8], [6], [9]. Acuity in health care can be described as both the number and degree of illnesses experienced by individual patients requiring acute care or the number of acutely ill patients a nurse is caring for during a shift.…”
Section: Workplace Challengesmentioning
confidence: 99%
“…Nurses are caring for patients with chronic illnesses who are frequently admitted with acute exacerbations of these conditions. In a comprehensive literature review of the lived experience of the transition of NGRNs in their first year of practice, Morrow [9] concluded that the exploration of the experience of new graduates in their first year of practice revealed ongoing challenges and historical inaction as nurses continue to be a marginalized and disenfranchised population. NGRNs are often overwhelmed not only by the numbers of patients they are expected to care for, but also by the acuity levels of patients who experience shorter lengths of stay despite complex challenges.…”
Section: Workplace Challengesmentioning
confidence: 99%